Cyclical TRIZ for brushless direct current motor evolution: From short-term adjustments to long-term transformation - Ilhan, Merve Yildiz; Altun, Koray (Society of Sytematic Innovation, 2025)
As engineering systems accumulate increasing layers of functional, structural, and behavioral complexity, the ability to guide their evolution with coherent, theory-driven frameworks has become essential. This paper presents a cyclical theory of inventive problem solving (TRIZ)-based roadmap for the evolution of brushless direct current (BLDC) motors, guiding development from short-term corrective actions to long-term transformative strategies. The approach structures action into three coupled cycles that respectively prioritize rapid technical remedies, system-level contradiction resolution, and strategic system transition, enabling engineers to align interventions with the maturity and scope of each design challenge. It fuses core TRIZ instruments with the trends of engineering system evolution to couple contradiction handling with forward trajectories of system ideality. Applied to automotive BLDC applications, the method organizes recurrent issues such as acoustic anomalies, modal coupling, thermal stress, and control-layout interactions into an actionable roadmap that scales from quick design adjustments to modular, artificial intelligence-enabled capabilities. Experimental validation confirms the method’s practical impact: acoustic noise in the H24 configuration decreased by approximately 13%, modal vibration in the H8 case reduced by nearly 28%, and rotational imbalance amplitude in the rotor-yoke assembly dropped by around 55% after structural and dynamic optimization. The resulting framework is both prescriptive and extensible, guiding short-term fixes without foreclosing mid-term harmonization or long-term transformation, and generalizes to electromechanical product families that must balance cost, noise, durability, and intelligence under evolving requirements. © 2025, Society of Sytematic Innovation. All rights reserved.
Keywords: Brushless Direct Current Motors; Cyclical Theory of Inventive Problem Solving; Roadmapping; Trends of Engineering System Evolution